ECTOPIC PREGNANCY IN A MALABARI DOE - NAVEEN KUMAR, R H; JAYAKUMAR, C; SHRAVYA, G S; SUDHA, C M (The Indian Journal of Animal Reproduction, 2017)
A Malabari doe with overdue pregnancy was presented with no typical evidence of kidding. On abdominal palpation, a firm mass was palpated which was tentatively diagnosed as ectopic pregnancy, and was further confirmed by trans-abdominal sonography. The ectopic fetus was removed by laparotomy. The presence of mesenteric vegetative attachments of placenta and completely involuted uterus without any uterine scar signified the occurrence of ectopic pregnancy at an early stage.